PEMBERIAN FEEDBACK SELAMA PEMBELAJARAN ONLINE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ABDURRAB PEKANBARU - Huda Marlina Wati; Juwaidah Hasibuan (LPPM Universitas Abdurrab, 2023)
Formative exams aim to improve learning processes and methods. From the data that has been obtained, summative test scores are influenced by formative exams. The purpose of the formative exam is to provide feedback in order to achieve these learning goals. During online learning students of the abdurrab university medical school conduct formative exams on each module. This study aims to find out how the effectiveness of formative exams by providing feedback during online learning to students of the Faculty of Medicine, Abdurrab University Pekanbaru. The method used in the study was quasi-experimental with a posttest only control group design. Sampling techniques by means of total sampling and different tests using Mann Whitney. The results of the study found that there was a significant difference between students' perceptions of formative exams given feedback and without giving feedback to students of the Faculty of Medicine, Abdurrab University Pekanbaru. The results of the correlation test obtained a p value of 0.000. There is a significant difference between students' perceptions of formative exams given feedback and without feedback.